Caries preventive potential of professionally deliverable fluoride-containing agents with incorporated arginine: A scoping review - Nouf Ali Alblooshi; Tiba Kahtan Naseer; Mohammed Nadeem Bijle (Elsevier, 2024)
The scoping review objectives were to: 1) investigate the caries preventive potential of professionally deliverable fluoride (F)-containing agents with incorporated arginine (Arg); and 2) identify the future scope of research on Arg-F interventions for caries prevention. Of 150 identified records, 7 articles (6 in vitro investigations and 1 scoping review) were included for a complete review; with no clinical studies with/without appraisal. Arginine variants (L-Arg/Arg.HCl at 1% to 10% w/v.) were examined for a potential professional application aimed at caries prevention, as reported with in vitro studies. Of the included articles, four in vitro studies explored L-Arg enriched 5% NaF varnish (Duraphat®) as a promising caries preventive agent, while only one considered incorporating L-Arg in MI varnish®/nanohydroxyapatite and one investigated glass ionomer cement for primary/secondary and tertiary caries prevention. The scoping review highlighted the scope for incorporating Arg to professionally deliverable F-containing agents. No clinical data are available to make conclusive recommendations about the caries preventive potential of professionally deliverable F-containing agents with incorporated Arg. With Arg-F varnish being investigated predominantly through in vitro studies, the data so far suggest that Arg was incorporated exclusively in Duraphat®, while the potential of Arg to prevent caries in other F-containing varnishes remains unexplored.